Effects of elevated concentrations of soybean molasses on feedlot performance and meat quality of lambs - Rodrigues, Julia Lisboa [UNESP]; Garcia Pereira-Junior, Sergio Antonio [UNESP]; Castro Filho, Edivilson Silva [UNESP]; Costa, Rayanne Viana [UNESP]; Barducci, Robson Sfaciotti [UNESP]; Castello Branco van Cleef, Eric Haydt; Bertocco Ezequiel, Jane Maria [UNESP] (Elsevier B.V., 2020)
The objective of this study was to investigate the effects of partial and total replacement of corn cracked grain with soybean molasses (SM) on performance and meat quality of feedlot finished lambs. Thirty crossbred lambs (Santa Ines x Dorper, three months old) were blocked by initial body weight (16.8 +/- 2.2 kg), and randomly assigned to three experimental treatments. During a 70-d experimental period, the animals were fed total mixed rations containing corn silage as forage source in a 40:60 (wt/wt) forage to concentrate ratio (dry matter basis). Dietary treatments consisted of different inclusion levels of soybean molasses: 0 g/kg DM (CON), 150 g/kg DM (SM15), or 300 g/kg DM (SM30). Lambs were slaughtered for evaluation of carcass characteristics and meat quality in Longissimus thoracis muscle. The inclusion of SM did not affect neither the feedlot performance nor the carcass quality, except for the gain to feed ratio, which decreased linearly (P = 0.05). The Longissimus muscle tenderness and intramuscular fat were linearly increased (P = 0.03, P < 0.01, respectively), with increasing SM in the diet. Linear trends for pentadecanoic, heptadecenoic, gamma linolenic and EPA acids (P = 0.07; P = 0.07; P = 0.07 and P = 0.09, respectively) were observed. Linear decrease was also observed for linoleic acid (P = 0.01). The addition of soybean molasses increased meat tenderness and intramuscular fat in crossbred feedlot finished lambs, when fed up to 300 g/kg DM, being a potential alternative to replace corn in feedlot diets, depending on its cost and availability.
Keywords: By-product; Intramuscular fat; Longissimus thoracis; Sheep; Sucrose; Stachyose